ANALISIS FAKTOR PENYELESAIAN SKRIPSI MAHASISWA PRODI PENDIDIKAN EKONOMI PPAPK - Kurniati, Dewi; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to determine the factors that influence the completion of the thesis FKIP PPAPK economic education students Untan. The research method used is descriptive research. Data sourch of this research is the 2014 PPAPK economic education students FKIP Untan. Data collection techniques used were interview techniques and documentation, while data collection tools used were interview guides and documentation. Analysis in this study was presented in a qualitative descriptive manner ussing 6 informants. The results of the study show that the factors influence the completion of the student?s thesis are: 1) motivation from within the student weakens when the student gets a lot of revision, in finding theories froom books that are difficult to obtain. 2) Student academic ability is quite good because students can formulate problems and determine research methods. 3) literature, teacher gets literature that is in accordance with the title of the thesis making students hampered to immediately complete the thesis. 4) Advisors in providing excellent services such as being able to provide input and can find out whrer the errors are, but the absence of a specific schedule to consult with the supervisor makes students difficult in thesis guidance Keywords: Completion of the thesis, Student